Public-key cryptography - PKC 2013 16th International Conference on Practice and Theory in Public-Key Cryptography, Nara, Japan, February 26 - March 1, 2013. Proceedings - Kurosawa, Kaoru; Hanaoka, Goichiro (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 16th International Conference on Practice and Theory in Public-Key Cryptography, PKC 2013, held in Nara, Japan, in February/March 2013. The 28 papers presented together with 2 invited talks were carefully reviewed and selected from numerous submissions. The papers are organized in the following topical sections: homomorphic encryption, primitives, functional encryption/signatures, RSA, IBE and IPE, key exchange, signature schemes, encryption, and protocols.